Selenium-Ethylene Interplay in Postharvest Life of Cut Flowers - Costa, Lucas C.; Luz, Luana M.; Nascimento, Vitor L.; Araujo, Fernanda F.; Santos, Mirelle N. S.; França, Christiane de F. M.; Silva, Tania P.; Fugate, Karen K.; Finger, Fernando L. (Frontiers in Plant Science, 2020)
Selenium (Se) is considered a beneficial element in higher plants when provided at low concentrations. Recently, studies have unveiled the interactions between Se and ethylene metabolism throughout plant growth and development. However, despite the evidence that Se may provide longer shelf life in ethylene-sensitive flowers, its primary action on ethylene biosynthesis and cause-effect responses are still understated. In the present review, we discuss the likely action of Se on ethylene biosynthesis and its consequence on postharvest physiology of cut flowers. By combining Se chemical properties with a dissection of ethylene metabolism, we further highlighted both the potential use of Se solutions and their downstream responses. We believe that this report will provide the foundation for the hypothesis that Se plays a key role in the postharvest longevity of ethylene-sensitive flowers.